085 Implementing a Knowledge Application Program for Anxiety and Depression in Community-Based Primary Mental Health Care: The Clinical Decision Support Component. (15th August 2013) - Roberge, P; Fournier, L; Brouillet, H; Benoit, A
Abstract : Background: We developed a knowledge application programme to support the improvement of the organisation and delivery of care for anxiety and depressive disorders in community-based primary mental health care teams (CMHTs) in Quebec (Canada). The programme is based on the Chronic Care Model, including a Decision Support component, and the PARiHS framework. Objectives: 1- To implement and evaluate a knowledge application programme, 2- to explore barriers and facilitators associated with the implementation of Decision Support strategies, particularly the uptake of clinical practice guidelines. Methods: The design is a mixed-methods prospective multiple case study, with data drawn from the two phases of the project (2008-2010; 2011-2014). Multidisciplinary local working committees in the six CMHTs were required to develop and implement local quality improvement plans with the support of a knowledge broker. Results: While we observed barriers and facilitators at the clinician level in terms of knowledge (e.g familiarity) and attitudes (e.g. applicability, agreement), contextual factors (e.g resources, access) also played an important role in the uptake of clinical practice guidelines into the six local CHMTs. Discussion: Decision Support is a central component of the Chronic Care Model that aims to promote clinical care that is consistent with scientific evidence. Implications: The uptake of evidence in primary care is a complex process that requires careful consideration of the context in which innovations are introduced, and our assessment of barriers and facilitators can be relevant to other primary health care organisations seeking to increase the uptake of anxiety and depression clinical guidelines.